Validated MicroRNA Target Databases: An Evaluation. Issue 7 (19th August 2015) - Ji (Diana) Lee, Yun; Kim, Veronica; Muth, Dillon C.; Witwer, Kenneth W.; Gurwitz, David
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> Positive findings from preclinical and clinical studies involving depletion or supplementation of microRNA (miRNA) engender optimism about miRNA‐based therapeutics. However, off‐target effects must be considered. Predicting these effects is complicated. Each miRNA may target many gene transcripts, and the rules governing imperfectly complementary miRNA: target interactions are incompletely understood. Several databases provide lists of the relatively small number of experimentally confirmed miRNA: target pairs. Although incomplete, this information might allow assessment of at least some of the off‐target effects. We evaluated the performance of four databases of experimentally validated miRNA: target interactions (miRWalk 2.0, miRTarBase, miRecords, and TarBase 7.0) using a list of 50 alphabetically consecutive genes. We examined the provided citations to determine the degree to which each interaction was experimentally supported. To assess stability, we tested at the beginning and end of a five‐month period. Results varied widely by database. Two of the databases changed significantly over the course of 5 months. Most reported evidence for miRNA: target interactions were indirect or otherwise weak, and relatively few interactions were supported by more than one publication. Some returned results appear to arise from simplistic text searches that offer no insight into the relationship of the search terms, may not even include the reported gene or miRNA, and may thus, be invalid. We conclude that validation databases provide important information, but not all information in all extant databases is up‐to‐date or accurate. Nevertheless, the more comprehensive validation databases may provide useful starting points for investigation of off‐target effects of proposed small RNA therapies. Drug Dev Res 76 : 389–396, 2015. © 2015 Wiley Periodicals, Inc.